Influência da anquiloglossia nas características do aleitamento materno em lactentes nos primeiros meses de vida - BATISTA , Christyann Lima Campos (2022)
Introduction: Ankyloglossia is a congenital disorder that limits the functional movements of the tongue. The prevalence can reach 8% in infants younger than 1 year. The alteration could lead to consequences such as problems in eating, speech, social skills, and oral health. Recent studies have investigated the effects of this anatomical alteration on breastfeeding, a feeding practice that improves the health of populations. In breastfeeding, changes have been reported that can cause pain, growth problems and even early weaning. Objectives: To analyze the influence of ankyloglossia on the continuation of Exclusive Breastfeeding (EBF) and on the evolution of infant growth (Chapter I) and to analyze the functional aspects of breastfeeding, self-efficacy and pain while breastfeeding in newborns according to severity of ankyloglossia (Chapter II). Methods: Prospective cohort study carried out at the University Hospital of the Federal University of Maranhão. In Chapter I, 225 infants and their mothers were followed up in the first six months of life. Full-term infants without congenital pathologies and mothers with no restrictions on breastfeeding were selected, and data from infants with and without the diagnosed alteration were compared. Data were collected on the duration of breastfeeding and measures of weight and length growth, and the Body Mass Index (BMI) and Z-scores of weight, length and BMI for age were also calculated. In Chapter II, a sample of 81 infants with ankyloglossia was selected, nested in the cohort of the first article, to assess aspects of breastfeeding according to the severity of the alteration. To assess the quality of breastfeeding, the LATCH Scoring System and the United Nations Children's Fund (BOF-UNICEF) Breastfeeding Observation Form were used. The perception of maternal pain was assessed by the Short Form of the McGill pain Questionnaire. Maternal self-perception of breastfeeding efficacy was measured by the Breastfeeding Self - Efficacy Scale -Short Form. In the data analysis, association measurements were performed using the Chi -square or Fisher's exact tests for categorical variables and Student 's T tests or the Mann-Whitney U test for continuous data. The repeated measures ANOVA test was used to assess growth measures. The odds ratio and relative risk for weaning were calculated. Regression analyzes included logistic and linear regression tests. The significance level adopted was 5% (p<0.05). Results: In Chapter I, it was observed that ankyloglossia was associated with weaning before the sixth month of life. After adjusted analysis, a higher risk of weaning was detected in babies with the present alteration (p<0.001, OR 4.49 95% CI = [2.29-8.80]). In the comparison of survival analysis, the duration of breastfeeding in children with ankyloglossia was shorter when compared to children without alteration (log-rank p<0.001). No significant differences were found in the growth measures among groups. In Chapter II, a significant association was detected only in the suction aspect evaluated by the BOF-UNICEF (p-value 0.013, β = 0.22 95% CI = [0.07-0.73]). It was also observed that the groups did not differ in the assessment performed by the LATCH scale and in the self-efficacy of breastfeeding (p>0.05). Pain scores also did not differ between the studied groups. Conclusion: Ankyloglossia was associated with weaning. Babies with the alteration had a shorter EBF time when compared to those who had a normal lingual frenulum, but it did not influence the babies' growth until 6 months of age. In the analysis of the severity of the alteration, it was observed that infants with severe ankyloglossia may have difficulties in the isolated aspect of sucking, but this alteration does not seem to affect the quality of breastfeeding, maternal self-efficacy or worsen the perception of pain when breastfeeding compared to with babies with mild alteration.